The Brondot Strategy: Achieving Victory Without Vote Buying in Indonesia’s Local Democracy - Rofiq, Rofiq; Nafisah, Nafisah (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2023)
This study employs a qualitative method with a case study approach on village head elections in two villages in Central Java to explore the role of the brondot strategy in democratization. This strategy utilizes rewards, primordial issues, and political clientelism to establish political hegemony, aiding incumbents in winning contests and avoiding significant competition, with hopes of victory without buying votes. Brondot is closely linked to familial political networks, leveraging biological relationships for network tactic control. Family's role in political elections and generational inheritance influences this strategy. The study provides insights into local political position elections without significant expenses, relevant in Indonesia where buying votes is a common practice.